Abdul Hameed Ansari revolutionary journalist and freedom fighter - Jamāluddīn, Jāvīd (Popular Prakashan, 2004)
On the life and works of ʻAbdulḥamīd Anṣārī, 1906-1972, Indian journalist and freedom fighter.